The Impact of Legal Status on Different Schooling Aspects of Adolescents in Germany - Homuth, Christoph; Welker, Jörg; Will, Gisela; von Maurice, Jutta (Refuge: Canada's Journal on Refugees, 2020)
During the so-called refugee crisis of 2015, approximately 300,000 underage asylum seekers came to Germany. We examine whether their legal status and their subjective perception of their status are equally important for their educational integration. On the basis of rational choice theory, we hypothesize that refugees’ legal status should affect their educational outcomes. Our study finds no differences among students with different legal statuses in school placement. However, students who perceive their status as insecure report significantly worse GPA than students who feel rather secure. Concerning the objective legal status, we do find that students with an insecure legal status report better grades than those with a granted refugee status. These contrary results show the importance of additionally considering status perception in understanding and explaining educational outcomes of immigrants in further research. Educators should be aware of the potential divergence between objective and subjective status and their corresponding effects on educational trajectories. **** Note that the original PDF version of this article contained a production error, which has now been fixed. As a result, the original pagination has been adjusted. ***